Causal relationship between genetic proxies for calcium channel blockers and the risk of depression: a drug-target Mendelian randomization study - Ye, Chaoyi; Wang, Tingjun; Wang, Huajun; Lian, Guili; Xie, Liangdi (Frontiers in Psychiatry, 2024)
Background: Calcium channel blockers (CCBs) are widely used in the clinical management of hypertension. Depression, a common comorbidity of hypertension, is an important issue in the management of hypertension. However, the impact of CCBs on depression risk remains controversial. We aim to investigate the causal effect of CCBs on depression through drug-target Mendelian randomization (MR) analysis. Methods: To proxy CCBs, we utilized the genetic variations located in or around drug target genes that were related to systolic blood pressure (SBP). Coronary artery disease (CAD) served as the positive control outcome. Genetic summary data of SBP, CAD, and depression were obtained from genome-wide association studies (GWAS) based on European population. Inverse variance weighted (IVW) method was applied as the main analysis to estimate the causal effect. Cochran’s Q test, MR-Egger intercept, MR pleiotropy residual sum and outlier (MR-PRESSO) and leave-one-out sensitivity analysis were used to test the robustness of the results. Meta-analysis was applied to further confirm whether causal relationships existed between CCBs and depression. Results: The IVW results failed to reveal any causal relationship between genetic proxies for CCBs and depression (P > 0.05). Cochran’s Q test showed no evidence of heterogeneity (P > 0.05). The MR-Egger intercept test suggested no evidence of directional pleiotropy, and the MR pleiotropy residual sum and outlier (MR-PRESSO) global test for horizontal pleiotropy was also not significant (P > 0.05). Leave-one-out analysis did not reveal any genetic variant that influenced the results. In addition, the meta-analysis further confirmed the absence of a causal relationship. Conclusion: The present study indicates no association of genetic proxies for CCBs with depression. Further studies are necessary to provide definitive evidence.